SARS-CoV-2 live virus neutralization after four COVID-19 vaccine doses in people with HIV receiving suppressive antiretroviral therapy. (1st April 2023) - Cheung, Peter K.; Lapointe, Hope R.; Sang, Yurou; Ennis, Siobhan; Mwimanzi, Francis; Speckmaier, Sarah; Barad, Evan; Dong, Winnie; Liang, Richard; Simons, Janet; Lowe, Christopher F.; Romney, Marc G.; et al.
Abstract : Objective: Limited data exist regarding the immune benefits of fourth COVID-19 vaccine doses in people with HIV (PWH) receiving antiretroviral therapy (ART), particularly now that most have experienced a SARS-CoV-2 infection. We quantified wild-type, Omicron-BA.5 and Omicron-BQ.1-specific neutralization up to 1 month post-fourth COVID-19 vaccine dose in 63 (19 SARS-CoV-2-naive and 44 SARS-CoV-2-experienced) PWH. Design: A longitudinal observational cohort. Methods: Quantification of wild-type-, Omicron-BA.5, and Omicron-BQ.1-specific neutralization using live virus assays. Results: Participants received monovalent (44%) and bivalent (56%) mRNA fourth doses. In COVID-19-naive PWH, fourth doses enhanced wild-type and Omicron-BA.5-specific neutralization modestly above three-dose levels ( P  = 0.1). In COVID-19-experienced PWH, fourth doses enhanced wild-type specific neutralization modestly ( P  = 0.1) and BA.5-specific neutralization substantially ( P  = 0.002). Consistent with humoral benefits of 'hybrid' immunity, COVID-19-experienced PWH exhibited the highest neutralization post-fourth dose, wherein those with Omicron-era infections displayed higher wild-type specific ( P  = 0.04) but similar BA.5 and BQ.1-specific neutralization than those with pre-Omicron-era infections. Nevertheless, BA.5-specific neutralization was significantly below wild-type in everyone regardless of COVID-19 experience, with BQ.1-specific neutralization lower still (both P  < 0.0001). In multivariable analyses, fourth dose valency did not affect neutralization magnitude. Rather, an mRNA-1273 fourth dose (versus a BNT162b2 one) was the strongest correlate of wild-type specific neutralization, while prior COVID-19, regardless of pandemic era, was the strongest correlate of BA.5 and BQ.1-specific neutralization post-fourth dose. Conclusion: Fourth COVID-19 vaccine doses, irrespective of valency, benefit PWH regardless of prior SARS-CoV-2 infection. Results support recommendations that all adults receive a fourth COVID-19 vaccine dose within 6 months of their third dose (or their most recent SARS-CoV-2 infection).